14.9k views
4 votes
PLEASE ANSWER QUICKLY WITH DESCRIPTION ON HOW TO DO IT!!! If (-a^2b3)(2ab^2)(-3b)=ka^mb^n what is the value of m+n????

PLEASE ANSWER QUICKLY WITH DESCRIPTION ON HOW TO DO IT!!! If (-a^2b3)(2ab^2)(-3b)=ka-example-1

1 Answer

3 votes

Answer:

m+n=9

Explanation:

Put the equation into the form ka^mb^n by multiplying the coefficients (-1*2*-3), so k= 6, then add the exponents of a together, a^2+a^1= a^3, m=3.

Now you have 6a^3, next we do the exponents of b together, b^3, b^2, b^1= b^6, n=6.

This is 6a^3b^6. m=3 and b=6, so add m+n=9.

User Alessandro Caliaro
by
6.3k points